Cert Prep: SOLIDWORKS Weldments. - Corbett, Gabriel (linkedin.com, 2017)
Prepare for the Certified SOLIDWORKS Professional Advanced Weldments (CSWPA-WD) exam, and master weldment techniques to design complex welded and bolted structures.